Compressive Strength Prediction of Square Concrete Columns Retrofitted with External Steel Collars - Pudjisuryadi, P.; Tavio . (Institute of Research and Community Outreach - Petra Christian University, 2013)
Transverse confining stress in concrete members, commonly provided by transverse reinforcement, has been recognized to enhance strength and ductility. Nowadays, the confining method has been further developed to external confinement approach. This type of confinement can be used for retrofitting existing concrete columns. Many external confining techniques have been proven to be successful in retrofitting circular columns. However, for square or rectangular columns, providing effective confining stress by external retrofitting method is not a simple task due to high stress concentration at column’s corners. This paper proposes an analytical model to predict the peak strength of square concrete columns confined by external steel collars. Comparison with the experimental results showed that the model can predict the peak strength reasonably well. However, it should be noted that relatively larger amount of steel is needed to achieve comparable column strength enhancement when it is compared with those of conve tional internally-confined columns.